Determining the Most Appropriate Spinning Reserve Depending on Demand - Tur, Melunet Rida; Erduman, Ali; Shobole, Abdulfetah; Wadi, Mohammed (IEEE, 2016)
In the deregulated power industry, effective procurement of the Ancillary Services (AS) is essential in order to both reliable supply to customer and power system security. AS arc used in order to operate the system reliably within enterprise safety along with the criteria regarding supply quality and operating conditions. Demand decrease set Spinning Reserve (SR) for power systems and capital cost investments and for all plants. Influential control of SR supply important cost decrease for large power systems. This study propose that set a reserve with the governor action and load shedding function depending on demand. This make possible the reliability of individual units and the uncertainty of the load forecast to the considered for short-term scheduling. While it is easy to implement decisive criterion, this situation does not conform to the structure prediction problems. Thus, the technique have been proposed for determining SR capacity depending on demand.
Keywords: Spinning Reserve; Ancillary Services; Load Shedding; Demand; Energy & Fuels